Determinants of Job Satisfaction in Professional Notary Service Organizations: Faktor-Faktor Penentu Kepuasan Kerja pada Organisasi Jasa Notaris Profesional - Shaudatul Aslamia; Rachmad Hidayat; Sri Rahayu (Indonesian Journal of Law and Economics Review, 2026)
General Background: Job satisfaction is a key factor in improving employee performance and professionalism, particularly in professional service organizations. Specific Background: At the Verra Sumenep Notary Office, the implementation of Flexible Working Arrangements, employer engagement, and employee productivity is assumed to influence employees’ job satisfaction. Knowledge Gap: Empirical studies examining these factors simultaneously in small notary offices remain limited. Aims: This study aims to analyze the effect of Flexible Working Arrangements, employer engagement, and employee productivity on employee job satisfaction at the Verra Sumenep Notary Office. Results: The results show that Flexible Working Arrangements, employer engagement, and employee productivity have a strong and significant positive effect on job satisfaction, indicating high levels of professionalism among employees. Novelty: This study provides evidence from a notary office context by integrating work flexibility, engagement, and productivity in a single research model. Implications: The findings suggest that improving work flexibility and employer engagement can enhance employee productivity and job satisfaction in professional service institutions. Highlights: Focus on job satisfaction in a notary office Positive impact of flexible work arrangements, engagement, and productivity Evidence from a small professional service organization Keywords: Flexible Working Arrangements, Employee Engagement, Employee Productivity, Job Satisfaction, Notary Office